1997
DOI: 10.1136/bmj.314.7087.1084
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, double blind, crossover challenge study of allergenicity of peanut oils in subjects allergic to peanuts

Abstract: Objective: To examine the effect of contact with a stroke family care worker on the physical, social, and psychological status of stroke patients and their carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(62 citation statements)
references
References 17 publications
2
58
0
1
Order By: Relevance
“…There might be thresholds for sensitization to an allergen and for triggering allergic reactions in sensitized individuals. Sensitization is difficult to observe in human populations; therefore, attempts have been made to establish thresholds for allergic reactions in humans, but with some limitations (57). In the absence of models for Cry9c, it has been suggested that the peanut allergen be used as a basis for exposure comparison for Cry9c: peanut allergy is prevalent in the United States and is known to cause severe reactions (34).…”
Section: Dose-response Assessmentmentioning
confidence: 99%
“…There might be thresholds for sensitization to an allergen and for triggering allergic reactions in sensitized individuals. Sensitization is difficult to observe in human populations; therefore, attempts have been made to establish thresholds for allergic reactions in humans, but with some limitations (57). In the absence of models for Cry9c, it has been suggested that the peanut allergen be used as a basis for exposure comparison for Cry9c: peanut allergy is prevalent in the United States and is known to cause severe reactions (34).…”
Section: Dose-response Assessmentmentioning
confidence: 99%
“…In most cases, roasted or fried peanuts are used because of their improved flavor and taste compared with their raw counterparts. Foods containing vegetable oil, however, may contain peanut proteins (10,21) that are not heated during processing. Therefore, peanut allergic individuals are exposed to both native and heat-treated peanut proteins and both can provoke allergic reactions.…”
mentioning
confidence: 99%
“…Some evidence highlighted that peanut oil (as well as the soybean oil) can not always be considered as a safe product for peanut-allergic patients (Hourihane 1997;Crevel 2000;Ring & Möhrenschlager 2007). Apart from a recent paper focused on the use of a biosensor (Bremer 2009), no specific data are available for protein content of either raw or refined HAO.…”
Section: Introductionmentioning
confidence: 99%